THE RELATIONSHIP BETWEEN SELF EFFICACY AND FAMILY SUPPORT IN PATIENTS WITH PULMONARY TUBERCULOSIS UNDERGOING TREATMENT AT PUSKESMAS CIMALAKA WEST JAVA - Luthfiah Yumna; Popon Haryeti; Heri Ridwan (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Tuberculosis has been discovered since the 19th century and there are clinical symptoms that indicate tuberculosis is a disease caused by the bacteria Mycobacterium tuberculosis. The research purposed to analyze the tie-in between self-efficacy and family support in pulmonary tuberculosis sufferers at the Cimalaka Health Center. The method used is a correlational descriptive research design involving 60 respondents selected using purposive sampling. Data was obtained using a questionnaire and then analyzed using Spearman's rank with a significance level of alfa ≤ 0.05. Based on the analytical calculations, it was found that p-value = 0.003 (< 0.005), which means there is a correlation between the self-efficacy variable and the family support variable with a degree of closeness of 0.377 (low). The results of the hypothesis test show that Ha is accepted, which means that the higher of- self-efficacy and the higher level of family support for pulmonary tuberculosis sufferers. For the next researchers are expected to be able to develop knowledge regarding the influence of self-efficacy on the effectiveness of treatment in pulmonary tuberculosis sufferers.